Altered levels of serum haptoglobin and apo A-I in schizophrenia - Tze Jen Chow,; Han Chern Loh, (Universiti Kebangsaan Malaysia, 2011)
Schizophrenia is a debilitating psychiatric syndrome that affects 1% of the world’s population. Abnormalities in immune functions and role of inflammatory markers have been widely described in schizophrenia. With the alarming high prevalence, this study aims to investigate the association of acute phase proteins with schizophrenia. We investigated the serum proteome of 20 schizophrenic patients and 20 healthy controls using two-dimensional gel electrophoresis and mass spectrometry. The spots were analysed using Image Master 2D Platinum software. In total, we have detected 774 protein spots in human serum and found that three of them showed altered changes in schizophrenic patients, as compared to healthy controls. Among these acute phase proteins, haptoglobin (p = 0.003) and two isoforms of apolipoprotein A-I (p = 0.004, p = 0.003) were found to be significantly decreased in patients, as compared to controls. Our findings support the hypothesis that inflammatory response system is linked to the pathophysiology of schizophrenia.